The Effect of Socioeconomic Factors on Household Health Expenditures: Heckman Two-Step Method - Mahdi Shahraki; Simin Ghaderi (Tehran University of Medical Sciences, 2019)
Background and Aim: Due to the high level of out-of-pocket payments for health expenditures and the importance of household health expenditure management, this study aimed to investigate socioeconomic factors affecting Iranian urban households' health expenditures. Materials and Methods: This descriptive-analytic and applied study was conducted cross-sectionally at national level with microeconomic approach. The sample included 18809 urban households living in Iranchr('39')s provinces in 2016; they were selected by three-stage sampling method. Data were collected by the household income-expenditure questionnaire of Statistical Center of Iran (SCI). The results were evaluated in Stata 14 software using Heckman two-step method. Results: The results showed that socioeconomic factors such as increasing of income and insurance expenditures, having insurance, number of employed people, headchr('39')s literacy, increasing of per capita expenditures of tobacco and education led to an increase in household health expenditures. Mother-headed households had lower health expenditures than others; and head of household's age, household size, and the presence of elderly persons led to an increase in household health expenditures. Conclusion: Household socio-economic factors not only affected the decision to enter health market but also influenced the purchase of goods and health services and inequality in health sector. Therefore, certain policies are essential to improve the socio-economic status towards reducing inequality in health sector; such a thing can be achieved through employment creation, growth of income, investment in education, and increase of insurance coverage.